Genome-wide association study in almost 195,000 individuals identifies 50 previously unidentified genetic loci for eye color - Simcoe, M; Valdes, A; Liu, F; Furlotte, NA; Evans, DM; Hemani, G; Ring, SM; Smith, GD; Duffy, DL; Zhu, G; Gordon, SD; Medland, SE; et al. (American Association for the Advancement of Science, 2021)
Human eye color is highly heritable, but its genetic architecture is not yet fully understood. We report the results of the largest genome-wide association study for eye color to date, involving up to 192,986 European participants from 10 populations. We identify 124 independent associations arising from 61 discrete genomic regions, including 50 previously unidentified. We find evidence for genes involved in melanin pigmentation, but we also find associations with genes involved in iris morphology and structure. Further analyses in 1636 Asian participants from two populations suggest that iris pigmentation variation in Asians is genetically similar to Europeans, albeit with smaller effect sizes. Our findings collectively explain 53.2% (95% confidence interval, 45.4 to 61.0%) of eye color variation using common single-nucleotide polymorphisms. Overall, our study outcomes demonstrate that the genetic complexity of human eye color considerably exceeds previous knowledge and expectations, highlighting eye color as a genetically highly complex human trait.